Is there equity in initial access to formal dementia care in Europe? The Andersen Model applied to the Actifcare cohort - Kerpershoek, Liselot (2022)
Funding: The project is supported through the following funding organizations under the aegis of JPND—www.jpnd.eu [grant number 733051001]. Germany, Ministry of Education and Research, Ireland, Health research board, Italy, Ministry of Health, the Netherlands, The Netherlands organization for Health Research and Development, Sweden, The Swedish Research Council for Health, Working Life and Welfare, Norway, The Research Council of Norway, Portugal, Foundation for Science and Technology (Fundação para a Ciência e Tecnologia [grant number FCT‐JPND‐HC/0001/2012], United Kingdom, Economic and Social Research Council. JPND has read and approved of the protocol of the Actifcare study.